2010
DOI: 10.1002/cne.22457
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the voltage‐gated potassium channel Kv2.2 in GABAergic neurons in the basal forebrain of rats and mice

Abstract: The Kv2 voltage-gated potassium channels, Kv2.1 and Kv2.2, are important regulators of neuronal excitability in mammalian brain. It has been shown that Kv2.1 channels are expressed in virtually all neurons in the brain. However, the cellular localization of Kv2.2 has not been fully elucidated. In this paper, we report that Kv2.2 is highly expressed in a subset of neurons in the magnocellular preoptic nucleus (MCPO) and the horizontal limb of the diagonal band of Broca (HDB) of the basal forebrain complex, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…The deduced size of Kv2.2 is 102.4 kDa (V5-tagged Kv2.2 is ϳ106 kDa), and we hypothesize that the lower of the two bands is the native Kv2.2 protein, whereas the higher band may represent a post-translationally modified form of the protein. Consistent with this interpretation, a similar, major band at 140 kDa has been shown to represent phosphorylated Kv2.2 protein in brain membrane fractions (30). Our data show that treatment Using the AdCMV-hKv2.2 adenovirus, we next investigated whether overexpression of Kv2.2 can rescue the impairment of GSIS caused by reduced ICDc expression.…”
Section: Kv22 Overexpression Rescues the Inhibitory Effects Of Siicdsupporting
confidence: 77%
“…The deduced size of Kv2.2 is 102.4 kDa (V5-tagged Kv2.2 is ϳ106 kDa), and we hypothesize that the lower of the two bands is the native Kv2.2 protein, whereas the higher band may represent a post-translationally modified form of the protein. Consistent with this interpretation, a similar, major band at 140 kDa has been shown to represent phosphorylated Kv2.2 protein in brain membrane fractions (30). Our data show that treatment Using the AdCMV-hKv2.2 adenovirus, we next investigated whether overexpression of Kv2.2 can rescue the impairment of GSIS caused by reduced ICDc expression.…”
Section: Kv22 Overexpression Rescues the Inhibitory Effects Of Siicdsupporting
confidence: 77%
“…This induced change in excitation/inhibition balance could modify both plasticity and function of forebrain circuits underlying cognition and emotion (Hensch, 2005, Sadrian et al, 2013). However, GABAergic neurons are also important for sleep-related oscillations and switching between sleep states (Hermanstyne et al, 2010, Halassa et al, 2011, Abel et al, 2013, Qiu et al, 2014, Brown and McKenna, 2015, Xu et al, 2015), and impaired function of GABAergic neurons impairs sleep (Kalume et al, 2015). If developmental EtOH exposure impairs GABAergic neuron function and/or reduces GABAergic cell number in subcortical areas known to regulate sleep, this may be an important link between early ethanol and sleep, as well as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The best characterized is JAK2-dependent phosphorylation of STAT3, the pathway that suppresses expression of the orexigenic peptides Npy and Agrp and promotes expression of the anorexigenic peptide POMC in the ARH (Myers et al, 2008) However, LepRb is coupled to several other signaling pathways, including phosphoinositide-3-kinase (PI3K), ERK, mTOR, and Src (Jiang et al, 2008;Myers et al, 2008;Heida et al, 2010;Heldsinger et al, 2011). Of these known signaling pathways coupled to LepRb, we considered Src to be a likely candidate for LepRb modulation of Kv2.1 as it has recently been established that Kv2.1 is phosphorylated by Srcfamily kinases (Tiran et al, 2003;Song et al, 2012) and it has been previously demonstrated that PI3K does not regulate Kv2.1 activity (El-Kholy et al, 2003).…”
Section: Kv21 Channels Contribute To the Leptin-sensitive Delayed Rementioning
confidence: 99%